The Influence of Fun at the Workplace among Employer and Employee / Rabiatul Adawiyah Ibrahim ...[et al.] - Ibrahim, Rabiatul Adawiyah; Mohd Wadzir, Siti Aisyah; Abd Wahab, Nurul `Izzati; Mohd Noor, Nur Esyawani (Universiti Teknologi MARA, 2020)
Fun at the workplace is a broad subject but specifically it plays a vital role in organizations as it can lead to benefit for both management and employees. The effects of fun at the workplace have led to a phenomenon that impacts both employees and the employer. It is noted that based on previous studies the literature on fun at the workplace has been mixed. This paper, therefore, will draw a theoretical framework that contributes to an understanding of fun at the workplace concept as a whole. This study further aims to determine how fun at the workplace gives impact within the organization and to further understand the benefits, values and desired outcomes of it. For this paper, structured questionnaires were distributed online through Google forms and were administered through LinkedIn, and Twitter to one hundred and five (105) respondents. Internal consistency was tested using Cronbach's alpha. The sample for this research was from a population who are working and not limited to any particular industry. The findings of the research prove that fun at the workplace increase the positive impacts among employees in Malaysia and is beneficial for the organizations as reference to foster suitable fun in the working environment.